Brain tumors induce immunoregulatory dendritic cells in draining lymph nodes that can be targeted by OX40 agonist treatment - Shokoufeh Karimi; Mats Hellström; Oscar Badillo-Godinez; Jenni Niemi; Liam Helfridsson; Mohanraj Ramachandran; Hitesh Bhagavanbhai Mangukiya; Sven Nelander (Journal for ImmunoTherapy of Cancer)
Background Primary and metastatic brain tumors have a poor prognosis, partly owing to the unique characteristics of the central nervous system (CNS) and tumor immune microenvironment (TIME). One distinct feature of the CNS TIME is the limited infiltration and activation of dendritic cells (DCs). The impact of CNS versus non-CNS TIME can be assessed by injecting tumor cells from the same model, either subcutaneously (peripherally) or into the brain. Subcutaneous tumors drain into the tumor-draining lymph nodes in the skin (TdLN-p), whereas brain tumors drain into the deep cervical TdLN (TdLN-c). We previously showed that CNS tumors that are not responsive to immune checkpoint inhibition become responsive when grown peripherally, and that non-responsiveness correlates with a tolerogenic immune response in the local TIME and TdLN-c.Methods In this study, we investigated the immunoregulatory potential of cervical DCs (DC-c) compared with that of peripheral DCs (DC-p) using high-resolution flow cytometry, single-cell RNA sequencing, and ex vivo and in vivo functional characterization of TdLNs from mouse models of glioma and lymphoma.Results Our analysis revealed that DC-c promoted regulatory T-cell expansion and poorly cytotoxic CD8+ T cells compared with DC-p. Furthermore, we identified OX40 (Tnfrsf4) as a modulator of immunoregulatory DC-c function and found that its antitumor effect depended on lymphocyte trafficking and the DC transcription factor Batf3. CCR7+OX40+ DCs were efficient in antigen processing and presentation, and OX40 agonists further enhanced DC activation. In TIME, the CCR7+OX40+ DCs expressed OX40L, and blocking it promoted Treg formation ex vivo.Conclusions Our findings highlight the unique immunoregulatory functions of DC-c in TdLNs and suggest the importance of OX40 signaling through direct effects on CCR7+OX40+ DCs and indirect effects on T cells.